Hidden storage side table with rattan open webbing for limited space / Norhafikah Sihabudin Surya - Sihabudin Surya, Norhafikah (2022)
Furniture, first and foremost, serves a purpose. It's an important part of the house, and its main purpose is to facilitate a variety of activities such as meals, amusements, recreation, research, and so on. People nowadays prefer furniture with a simple and aesthetic design that also serves multiple functions. This study aims to produce a hidden storage side table with a combination of rattan open webbing and rubberwood that has an aesthetic, unique design and a wide range of uses. As a result, a questionnaire form was distributed via Google form to 103 potential customers in order to direct them to the proposed side table of new look variations. The descriptive analysis results show that design and function are important factors in creating a concealed storage side table with rattan open webbing. Meanwhile, correlation analysis results show that there is a significant positive relationship between knowledge, materials, and design and potential customer satisfaction. As a result, it is hoped that the proposed product will be marketed in the same way as other marketable furniture.